Evaluation of Alkali/Surfactant/Polymer Flooding on Separation and Stabilization of Water/Oil Emulsion by Statistical Modeling - Al-Kayiem, H.H. (American Chemical Society, 2017)
Alkali/Surfactant/Polymer flooding is a chemical method for enhanced oil recovery. This study emphases the sensitivity of Alkali/Surfactant/Polymer flooding for the separation and stabilization of light oil emulsion in the primary gravity separator. A laser scattering technique by Turbiscan was used to determine the sedimentation of the water phase. A statistical modeling has been carried out to find the effectiveness of Alkali/Surfactant/Polymer on water in oil emulsion. The results show that the presence of alkali has a positive but insignificant effect on destabilization of emulsion in the concentration range from 500 to 1500 ppm. The addition of weak alkali, Na2CO3, is less problematic for separation. It was found that surfactant alone and surfactant-surfactant cross-interaction were the most significant additives causing reduction of water separation. However, the interaction effects between the alkali and surfactant, between the surfactant and polymer, and between polymer and polymer had significant influences on the water separation. An anionic hydrolyzed polyacrylamide polymer flooding has a positive effect on separation in the presence of low water cut and light crude oil emulsion. Polymer shows a positive effect on separation but the clarity (light transmission fraction) of the separated water is reduced. The clarity of the separated water is more than 83 and around 69 at 400 and 800 ppm polymer concentrations, respectively. Increase in alkali and surfactant has insignificant effect on the clarity of separated water. Based on the statistical model, empirical correlations were developed to predict the separation of water. © 2017 American Chemical Society.